Decarbonizing the Global Electricity Sector through Demand-Side Management: A Systematic Critical Review of Policy Responses [Penyahkarbonan Sektor Elektrik Global Melalui Pengurusan Sebelah Permintaan: Kajian Kritikal Sistematik Terhadap Tindak Balas Dasar] - Said F.F.; Babatunde K.A.; Nor N.G.Md.; Mahmoud M.A.; Begum R.A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper provides an up-to-date and comprehensive systematic literature review (SLR) of the existing research on long-term electricity decarbonization which is dominated by the global scenarios of Integrated Assessment Models. The aim is to synthesize and extend current understanding on the existing supply-side solutions and demand-side technological options despite the broader range of co-benefits and the latters lesser risk. We achieve this by adopting a two-step systematic literature review approach to analyse and review SLR datasets consisting of 103 empirical studies conducted in Asia, Europe, and North America countries in economics and environmental economics from 1994 to 2018 and published in Web of Science and Scopus indexed journals. We find that demand-side policy studies are predominantly carried out in Asia, Europe, and North America. The US contributes more than one-quarter of the studies reviewed, most of which were published after US withdrawal from the Paris Agreement. Three types of Demand-Side Management (DSM) are identified namely energy efficiency, energy conservation, and demand response policies. The corresponding policy instruments can be categorised into six basic categories. We further found that these instruments are not always implemented for emissions reduction. In addition, energy-saving is found to be the reason for DSM implementation. The findings suggest that demand-side solutions through policies need to be fully exploited to achieve carbon emission targets from the electricity sector or energy sector in general. 2022 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.